Subtelomeric rearrangements of dysmorphic children with idiopathic mental retardation reveal 8 different chromosomal anomalies - Mihçi, Ercan; Ozcan, Mualla; Berker-Karaüzüm, Sibel; Keser, Ibrahim; Taçoy, Sükran; Hapsolat, Senay; Lüleci, Güven (The Turkish Journal of Pediatrics, 2009)
Subtelomeric rearrangements are an important cause of both sporadic and familial idiopathic mental retardation (MR) and/or congenital malformation syndromes. We report on a cohort of 107 children with idiopathic MR and normal karyotype 450-550 band level by GTG banding screened for subtelomeric rearrangements by multiprobe fluorescence in situ hybridization (FISH). In these cases, five patients had de novo deletions (1p deletion was found in 2 cases; 3q deletion, 9p and 9q deletions were found in 1 case each) and four patients had unbalanced rearrangements [der(5)t(5;15)(pter;qter)pat in 2 patients who were siblings, rec(10)dup(10p)inv(10)(p13q26)mat in 1 patient and der(18)t(18;22)(qter;qter) de novo in 1 patient]. Our study confirms that the subtelomeric rearrangements are a significant cause of idiopathic MR with dysmorphic features.